2003
DOI: 10.1002/humu.9204
|View full text |Cite
|
Sign up to set email alerts
|

NDP gene mutations in 14 French families with Norrie disease

Abstract: Norrie disease is a rare X‐inked recessive condition characterized by congenital blindness and occasionally deafness and mental retardation in males. This disease has been ascribed to mutations in the NDP gene on chromosome Xp11.1. Previous investigations of the NDP gene have identified largely sixty disease‐causing sequence variants. Here, we report on ten different NDP gene allelic variants in fourteen of a series of 21 families fulfilling inclusion criteria. Two alterations were intragenic deletions and eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…To date, over 70 pathogenic NDP mutations have been identified. [8][9][10] Accessory phenotypes in 'classical' ND include progressive sensorineural deafness in approximately one-third of cases and some degree of intellectual disability, autism or psychosis in over 50% of cases. 11 Atypical ND patients with a contiguous deletion of NDP and both MAO genes present with a more severe neurological involvement, with profound psychomotor and verbal deficits.…”
Section: Introductionmentioning
confidence: 99%
“…To date, over 70 pathogenic NDP mutations have been identified. [8][9][10] Accessory phenotypes in 'classical' ND include progressive sensorineural deafness in approximately one-third of cases and some degree of intellectual disability, autism or psychosis in over 50% of cases. 11 Atypical ND patients with a contiguous deletion of NDP and both MAO genes present with a more severe neurological involvement, with profound psychomotor and verbal deficits.…”
Section: Introductionmentioning
confidence: 99%
“…The NDP gene, located on chromosome Xp11.1 [Bleeker‐Wagemakers et al, 1985], was identified by positional cloning by two groups [Berger et al, 1992; Chen et al, 1992]. Extensive investigations of the two coding exons of the NDP gene have led to the identification of at least 70 disease causing mutations in ND patients [Schuback et al, 1995; Royer et al, 2003; Riveiro‐Alvarez et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The anomalies caused by Norrie disease (a syndrome associated with X-linked HL) include bilateral blindness, bilateral sensorineural HL, mental retardation and microphthalmia [96,97]. Poor growth, microcephaly, seizures, delay in sexual maturity, cardiovascular problems, pulmonary arterial hypertension and psychomotor retardation like complex symptoms are also seen in some patients [98][99][100][101][102][103][104][105]. Patients affected by AR Biotinidase deficiency syndrome shows the signs like deafness, hair loss, seizures, emesis, skin rashes and acidosis.…”
Section: Clinical Features Of Deafnessmentioning
confidence: 99%